Clinical experience with single-port access laparoscopic cystectomy and myomectomy - Jeong, Jae-Hyeok (Clin Exp Reprod Med, 2016)
OBJECTIVE: This study was performed to assess our clinical experience with single-port access (SPA) laparoscopic cystectomy and myomectomy and the surgical outcomes of those procedures at our institution. METHODS: The authors evaluated the surgical outcomes of SPA laparoscopic cystectomy in 293 patients and SPA laparoscopic myomectomy in 246 patients. The surgical outcomes comprised operation time, the amount of blood loss during the operation, the change in hemoglobin (before and after the operation), the change in hematocrit (before and after the operation), switching to the multi-port access method, complications, transfusions, and the duration of the postoperative hospital stay. RESULTS: The Pearson correlation coefficient and the Spearman correlation coefficient between the operation time and the amount of blood loss were 0.312 and 0.321 for SPA laparoscopic cystectomy, respectively, and 0.706 and 0.674 for SPA laparoscopic myomectomy, respectively. The drops in hemoglobin and hematocrit were 1.33±0.78 g/dL and 4.14%±2.45%, respectively, in SPA laparoscopic cystectomy, while the corresponding figures were 1.34±1.13 g/dL and 4.17%±3.24% in SPA laparoscopic myomectomy, respectively. CONCLUSION: This study reported the surgical outcomes of SPA laparoscopic cystectomy and myomectomy and compared them to previously published findings on traditional laparoscopic cystectomy and myomectomy. No significant differences were found in the surgical outcomes between SPA and traditional laparoscopic cystectomy and myomectomy.